Nonenzymatic sensor for hydrogen peroxide using a carbon paste electrode modified with a composite consisting of silver nanoparticles, poly(o-aminobenzoic acid) and magnetite - Sanoe Chairam (2018)
© 2015 The Authors. A nonenzymatic hydrogen peroxide (H2O2) sensor using a carbon paste electrode (CPE) modified with a composite consisting of silver nanoparticles (AgNPs), poly(o-aminobenzoic acid) (P(ABA)) and magnetite (Fe3O4) is reported. The AgNPs-P(ABA)-Fe3O4 composite was prepared under sonication and characterized using transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and vibrating sample magnetometer (VSM). Electrochemical investigations indicated that a carbon paste electrode modified with AgNPs-P(ABA)-Fe3O4 exhibits excellent performance in the electrochemical reduction of H2O2 at an applied potential of -0.4 V versus Ag/AgCl (sat. 3.0 M KCl) in phosphate buffer solution. Under optimum condition, the calibration curve for H2O2 was obtained in a wide range of 5 μM to 5.5 mM with the limit of detection (LOD) of 1.74 μM (S/N = 3). The AgNPs-P(ABA)-Fe3O4 modified electrode has a good stability in practical conditions. In addition, the fabricated sensor was applied to determine H2O2 in real samples with good results.